Youth Unemployment, Violent Extremism and Job Creation For Peace and Prosperity- Silatech as a Case Study - Abdelkarim, Abbas (International Journal of Scientific Research and Management (IJSRM), 2017)
The first section of this Paper portrays the youth unemployment situation in the Arab region. The scale of youth unemployment in the Arab region, being more than double the average world rate, justifies why Silatech, the case study of the Paper, has decided to start focusing on the region despite being launched by its initiator as an international youth-oriented initiative, a role that still Silatech endeavours to move onto.The second section exposes violent extremism as a threat to global peace and security. It also shown that youth represent a primary recruitment target of violent extremists. While youth unemployment may be a push factor leading to violent extremism, it has been argued that there are other push and pull factors that need to be understood and considered when developing strategies and interventions to prevent and combat violent extremism.The third section affirms employment creation as a priority for peace, security and for attaining global sustainable development goals. It discusses and draws lessons from donor youth programming.The fourth section present the activities and the organisation of operations of Silatech, as an organisation that works in the economic empowerment of youth.Two points make the conclusion: the employment promotion role of Silatech as peacebuilding; helping in preventing and dealing with the consequences of violent extremism, and how can Silatech avoids two of the negative international experiences in youth development programmes